SUCCESSION MANAGEMENT: UPAYA HUMAN RESOURCE PLANNING MENUJU SUCCESS CORPORATE - Kuswati, Rini (Benefit, 2009)
The changes of the business environment, societal expectations, and internal processes,Â cooperationare redesigningÂ theirÂ successionÂ planningÂ to remaincompetitiveÂ inÂ developingÂ strongÂ leadershipÂ teams.ByÂ movingÂ to successionÂ management,Â corporationscreateÂ a more flexible and dynamic approach for preparing future executive and have the leadership necessary ready to meet the business challenges of the remainder of the decade and beyond. Succession management allows the corporate leadership to instill a more dynamic process became easier to integrate with the firmâs strategic initiatives. It better aligns organizational thinking with the external environment where the discontinuities make it possible to anticipate the full spectrum of change that a corporation will confront. It is the leadership and succession philosophy that focuses on developing the creativity and flexibility that allows for a more rapid response to change. So succession management as one way to became the success corporate.